Outcome of Liposuction for Limb Lymphedema in Men Compared with Women - Helen Mackie; Belinda M. Thompson; Robyn Ricketts; Kim Toyer; Asha Heydon-White; Louise A. Koelmeyer; Thomas C. Lam (Journal of Plastic and Reconstructive Surgery)
Objectives: Liposuction effectively reduces limb volume in cases of advanced fat-dominant lymphedema. This study compares surgical outcomes between men and women using Brorson's liposuction for lymphedema protocol. Methods: A total of 11 men and 11 women with unilateral limb lymphedema who underwent liposuction were matched based on preoperative volume difference (Vol Diff) and percentage volume difference (%Vol Diff) between the affected and unaffected limbs. Individuals were secondarily matched for age, body mass index, and lymphedema duration. The volume of fat aspirated was compared to preoperative Vol Diff to calculate a percentage (%) aspirate volume. The preoperative %Vol Diff and postoperative %Vol Diff at two-time intervals over 12 months were recorded. Differences between the groups were assessed for significance. Results: Preoperative male group mean %Vol Diff of 35.1% matched the female group mean %Vol Diff of 34.8% (p = 0.928). The surgical male mean %aspiration volume of 80.4% was significantly less than the female group of 119% (p = 0.004). The reduction in male mean %Vol Diff was significantly less at the two postoperative time intervals. At 3-6 months, the mean %Vol Diff for men was 20.7% and 3.8% for women (p = 0.009). At the 9-12 months, the mean %Vol Diff was 13.2% for men and 4.2% for women (p = 0.006). Conclusions: The male group matched for preoperative volume with a female group had a lower %aspiration volume and higher postoperative %Vol Diff which was most likely due to sex-based fat differences.